Application of Appreciative Learning Approach in Computer Games Development Towards Promoting Student Creativity and Intrinsic Motivation - Eow, Yee Leng (2011)
The purpose of this action research study was to understand the application of appreciative learning approach in computer games development environment towards promoting of form one gamer students’ creativity (product’s creativity, creative perception, and creative process) and intrinsic motivation. Subsequently, actions were taken to improve the application of appreciative learning approach in computer games development environment, attuned to the subjects’ needs and preferences. The study consisted of three cycles and the subjects were form one gamer students. Instruments used were Computer Game Assessment Inventory (product’s creativity), Khatena-Torrance Creative Perception Inventory (creative perception), Creative Process Instrument (creative process), and Intrinsic Motivation Inventory (intrinsic motivation). Qualitative methodology was incorporated to build better understanding on the improvement possibilities for appreciative learning approach in computer games development environment towards promoting of form one gamer students’ creativity and intrinsic motivation. Therefore, qualitative data were derived from interviews, students’ products, logbooks, and visual captures. Actions taken at each cycle of the study were based on both quantitative and qualitative data gathered from the students as the main stakeholders, Paired-samples t-test analyses using SPSS 15.0 displayed remarkable promoting of students’ creativity and intrinsic motivation at an alpha level of .05 from cycle to cycle for products creativity (mean score of 4.22 4.82 5.50); creative perception (mean score of 71.82 74.53 76.90); creative process (mean score of 3.83 4.27 4.58); and intrinsic motivation (mean score of 6.02 6.20 6.50). Qualitative data gathered justified the statistical data as well. It indicated that most students’ needs and preferences were fulfilled; and problems faced were minimised through from cycle to cycle. Students favoured design stage the most and disliked dream stage. Qualitative data also served as credibility assurances to quantitative data. Findings from this action research study concluded appreciative learning approach in computer games development environment as having the potential in promoting the form one gamer students’ creativity (product’s creativity, creative perception, and creative process) and intrinsic motivation. Nevertheless, throughout the study, while actions taken were successfully working out with some students, it caused glitches on others. The change process in action research has an open starting point and no absolute ending point. As a result, there are still probable actions to be undertaken to generate transformational possibilities for appreciative learning approach as a pedagogical strategy in future researches.